Implementation of Web-Enhanced Course-Based Virtual Reality for Entrepreneurship Learning to Create Islamic Social Entrepreneur in The New Normal - Kusdiyanti, Heny; Nurruddin Zanky, Mokhammad; Febrianto, Indra; Wijaya, Robby (KnE Social Sciences, 2021)
The aim of this research was to develop interactive learning media by using web- enhanced and virtual reality technology, in order to promote young entrepreneurship in this new normal era. A descriptive approach was used and data were collected from teachers and students. The media that was developed can change the economic behavior and lifestyle of high school students through promoting profitable entrepreneurial activities. The results showed that teacher competence was increased. There are several components of the implementation process, such as the delivery of material, interaction with the material, interaction with a teacher, interaction with other students, and intra-action. The results showed that the implementation of the learning media increased teacher and student activity in entrepreneurship learning. The results were shared with other researchers and the government to encourage them to participate and take initiative to implement entrepreneurship learning by using this technology. Keywords: Disruptive Learning, MSME’s, Virtual Reality, Web-Enhanced